Corporate governance disclosure and information asymmetry: Evidence from South Africa - Vos, Ashleigh (Department of Finance and Tax, 2024)
Investors globally are becoming more interested in companies' governance disclosure, in part to reduce the information asymmetry caused by the principal-agent problem. Although the association between a company's governance disclosure and its level of information asymmetry has been explored in some developed countries, there is a gap in knowledge on this in a developing country context. This study investigates this link for companies listed on the Johannesburg Stock Exchange (JSE). Using Tobin's Q and share price volatility as proxies for information asymmetry; Bloomberg governance disclosure scores as the variable of interest; and board size, board independence, audit committee size, analyst following, systematic risk, free float, the inverse of assets and profitability as control variables, panel data regression methodology is applied to a sample of 103 companies listed on the JSE from 2009 to 2021 in order to explore the relationship between governance disclosure and information asymmetry in South Africa. Random effects panel regression is used for each dependent variable (share price volatility and Tobin's Q) to gain an understanding of the relationship between corporate governance disclosure, the control variables, and the proxies for information asymmetry. The results of each regression showed that there is a negative correlation between governance disclosure and dependent variables (share price volatility and Tobins Q). This was in line with the hypothesis for the dependent variable - share price volatility, however, the Tobin's Q regression produced a negative correlation when the hypothesis stated a positive correlation. The Tobin's Q regression shows mixed results and therefore there is not sufficient evidence to confirm the hypothesis stated. Since both regression results produced negative results, it contributed to existing literature that prioritising good governance practices will allow a firm to gain the support of stakeholders and reduce information asymmetry.